OPTIMALISASI PEMANFAATAN LAHAN MELALUI PENERAPAN SISTEM AGROFORESTRI DI DESA LAMBAKARA KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Nur Arafah; Sahindomi Bana; Umar Ode Hasani; Abdul Manan; Nurhayati Hajar; Asrianti Arif; Lade Ahmaliun; La Gandri; Herlan Hidayat; Muhamad Saleh Qadri (Jurnal Pengabdian NUSANTARA, 2022)
Land use must take into account the ecological, economic and socio-cultural factors of the community. Optimization of ecologically effective land use can provide a soil protection function to maintain soil fertility so that crop yields are maintained without damaging the environment. While economically it can help meet the needs of the household community at a certain time and in the long term. The socio-cultural considerations of the community are considered in order to fulfill the preferences and technology owned by the community in utilizing their land through the agroforestry system. The purpose of this activity is to educate the community about the importance of land management with agroforestry systems. The method used in this activity is a participatory approach through real action involving village officials and local communities. Indicators of the implementation of this program running smoothly can be seen from the involvement of the Lambakara Village government and community members in the activity program starting from the introduction of activities, socialization and training on the application of agroforestry. This activity has also carried out the planting of 1000 trees with an agroforestry approach consisting of 300 nutmeg seedlings, 200 areca nut seedlings, 300 teak seedlings, and 200 red jabon seedlings.